2019
DOI: 10.1097/coc.0000000000000553
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Rituximab-associated Gastrointestinal Toxicities

Abstract: Background: Rituximab is effective in treating several cancers. Little is known about gastrointestinal adverse events associated with rituximab. We describe the clinical, endoscopic, and histologic features of rituximab-associated colitis (RC) at a tertiary care cancer center. Methods: We conducted a retrospective study of cancer patients who had received rituximab and had undergone a colonoscopy between 2000 and 2018. Patients with competing etiologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…The GIP of rituximab therapy is rare but there, and several case reports indicated a possible association between rituximab and GIP (54)(55)(56). Although rare, rituximab might be associated with colitis that can be severe enough to cause colon perforation (57). Noteworthy, axicabtagene ciloleucel, one of the CAR-T therapies, was detected with the potential GIP signals in our study.…”
Section: Journal Of Pharmacy and Pharmaceutical Sciencessupporting
confidence: 52%
“…The GIP of rituximab therapy is rare but there, and several case reports indicated a possible association between rituximab and GIP (54)(55)(56). Although rare, rituximab might be associated with colitis that can be severe enough to cause colon perforation (57). Noteworthy, axicabtagene ciloleucel, one of the CAR-T therapies, was detected with the potential GIP signals in our study.…”
Section: Journal Of Pharmacy and Pharmaceutical Sciencessupporting
confidence: 52%
“…RTX is usually well-tolerated but that adverse events can occur, such as severe mucocutaneous reactions, infusional reactions, progressive multifocal leukoencephalopathy, acute respiratory distress syndrome and cardiovascular events. Recently, RTX has also been associated with adverse gastrointestinal effects, including diarrhea and bowel perforation, and recent reports have associated RTX with the development of de novo IBD [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…23,24 As an effective CD20 antagonist, rituximab impacts B cells in mucosa-associated lymphoid tissues as well as B-cell non-Hodgkin lymphoma. 24 Limited cases 25 have reported that rituximab can slightly injure digestion functions, such as dyspepsia and diarrhea. However, the cross-talking between intestinal B cells and gastrointestinal microbiota and rituximab still needs to be elucidated.…”
Section: Introductionmentioning
confidence: 99%